1987
DOI: 10.1002/j.1556-6676.1987.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Work Values and Career Maturity of 9th‐ and 11th‐Grade Boys and Girls

Abstract: Sex differences in work values and career maturity were found to a greater extent than were grade differences among 9th‐ and 11th‐grade students. Implications for counselors are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
2
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 6 publications
5
35
2
4
Order By: Relevance
“…Consistent with the biological and psychological maturation process, during the adolescence and early adulthood period when people are mainly undergoing education and training process, there should be a normative value change toward expanding the self and gaining more information. For example, Post-Kammer (1987) reported that 11 th -grade students reported valuing intrinsic work values to a greater extent than did the 9 th -grade students. Sheldon (Sheldon et al, 2003;Sheldon & Kasser, 2001;Sheldon, 2005) has studied value changes in adolescence and early adulthood, finding that liberal environment and opportunity for sophisticated thinking in college is not supportive of materialistic and extrinsic values but promotes the development of intrinsic values.…”
mentioning
confidence: 99%
“…Consistent with the biological and psychological maturation process, during the adolescence and early adulthood period when people are mainly undergoing education and training process, there should be a normative value change toward expanding the self and gaining more information. For example, Post-Kammer (1987) reported that 11 th -grade students reported valuing intrinsic work values to a greater extent than did the 9 th -grade students. Sheldon (Sheldon et al, 2003;Sheldon & Kasser, 2001;Sheldon, 2005) has studied value changes in adolescence and early adulthood, finding that liberal environment and opportunity for sophisticated thinking in college is not supportive of materialistic and extrinsic values but promotes the development of intrinsic values.…”
mentioning
confidence: 99%
“…A large amount of the literature found the above intrinsic motivational factors characterized intrinsically motivated people to be happy and satisfied with their jobs (Post-Kammer, 1987;Ross, 2005;Ryan & Deci, 2000;Wiley, 1997;Yousaf et al, 2015;Zhao & Zhu, 2014). However, many HTM programme students will not feel a sense of achievement as one kind of intrinsic content factors from repetitive tasks, and are bored with this daily work (Bloom et al, 2009;Lam & Ching, 2007).…”
Section: Intrinsic Motivational Factorsmentioning
confidence: 99%
“…Among the literature on career research, extrinsic factors are always line with career success rather than with career decisions (Hirschi, 2010;Lewis et al, 2001;O'Reilly & Caldwell, 1980;Post-Kammer, 1987;Randolph & Johnson, 2005). Thus, based on the literature reviewed, extrinsic factors represent personal objective components, in terms of payment, benefits, promotion, occupational status, respect and recognition by the organization, can lead directly to an individual's career success (O'Reilly & Caldwell, 1980).…”
Section: Extrinsic Motivational Factors and Career Decisionsmentioning
confidence: 99%
“…7, n° 1, 1994 résolument instrumentale : le travail futur servira en premier lieu à gagner de l'argent (Csikszentmihalyi et Larson, 1984;Hladlum, 1990). Cette valorisation des aspects avant tout financiers du travail serait plus courante chez les garçons, alors que chez les filles, le sentiment d'accomplissement personnel serait plus important (Mannheim et Seger, 1993;Nevill et Perotta, 1985 ;Post-Kammer, 1987). …”
Section: Comment Perçoit-on Le Travail à L'adolescence?unclassified